The impact of exchange rate uncertainty on exports: a panel VAR analysis - Muinelo-Gallo, Leonel; Miranda Lescano, Ronald; Mordecki, Gabriela (Estudios de Economía, 2020)
In this paper we analyze the impact of exchange rate uncertainty on export flows among a panel of 27 countries throughout the 1994/01-2014/12 period. In order to do this, we apply a panel vector autoregressive model approach. By dividing the panel into two subgroups that involve manufacturing-exporting and commodity-exporting economies, we observe a different effect of exchange rate uncertainty on exports. This has a negative impact in manufacturing-exporting countries, but does not affect commodity exporting countries. This result appears to be explained by countries’ economics characteristics, involving the flexibility or rigidities of the export adjustment arising exchange rate uncertainty.